Comparison of the Molecular Dynamics and Calculated Binding Free Energies for Nine FDA‐Approved HIV‐1 PR Drugs Against Subtype B and C‐SA HIV PR. (19th November 2012) - Ahmed, Shaimaa M.; Kruger, Hendrik G.; Govender, Thirumala; Maguire, Glenn E. M.; Sayed, Yasien; Ibrahim, Mahmoud A. A.; Naicker, Previn; Soliman, Mahmoud E. S.
<x xml:space="preserve">Abstract</x> We report the first account of a comparative analysis of the binding affinities of nine FDA‐approved drugs against subtype B as well as the South African subtype C HIV PR (C‐SA). A standardized protocol was used to generate the inhibitor/C‐SA PR complexes with the relative positions of the inhibitors taken from the corresponding X‐ray structures for subtype B complexes. The dynamics and stability of these complexes were investigated using molecular dynamics calculations. Average relative binding free energies for these inhibitors were calculated from the molecular dynamics simulation using the molecular mechanics generalized Born surface area method. The calculated energies followed a similar trend to the reported experimental binding free energies. Postdynamic hydrogen bonding and electrostatic interaction analysis of the inhibitors with both subtypes reveal similar interactions. Most inhibitors show slightly weaker binding affinities for C‐SA PR. Molecular dynamics studies demonstrated increased flap movement for C‐SA PR, which can perhaps explain the weaker affinities. This study serves as a standardized platform for optimizing the design of future more potent HIV C‐SA PR inhibitors.